MAKNA KRITIK SOSIAL DALAM PUISI (Studi Analisis Wacana Kritis pada Puisi “Dongeng Marsinah” Karya Sapardi Djoko Damono) - Alfiansyah Alfiansyah; Hamidah Hamidah; Indrawati Indrawati (Program Studi Jurnalistik, Universitas Islam Negeri Raden Fatah Palembang, 2020)
ABSTRACT This research was started from the authors’ interest in social criticisms related to the case of human rights violations experienced by the watch factory worker from PT. Catur Putra Surya (CPS) named Marsinah during the New Order period. Poetry itself is one of the communication media that can be used by someone to give social criticism against an occasion. In a poem